2023
DOI: 10.3389/fimmu.2023.1133297
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes in liver fibrosis: The role of modulating hepatic stellate cells and immune cells, and prospects for clinical applications

Abstract: Liver fibrosis is a global health problem caused by chronic liver injury resulting from various factors. Hepatic stellate cells (HSCs) have been found to play a major role in liver fibrosis, and pathological stimuli lead to their transdifferentiation into myofibroblasts. Complex multidirectional interactions between HSCs, immune cells, and cytokines are also critical for the progression of liver fibrosis. Despite the advances in treatments for liver fibrosis, they do not meet the current medical needs. Exosome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 108 publications
(163 reference statements)
0
8
0
Order By: Relevance
“…Similar to parental MSC activity, MSC-derived exosomes [ 45 , 46 ] function as a mediator of intercellular communication between MSC and injured organ sites, which exerts effectiveness in various animal models of liver disease including acute liver damage, hepatic fibrosis, and hepatocellular carcinoma [ 47 50 ]. Typically, Exosomes are easier to obtain and store, and inherited with qualities like high reparability and low immunogenicity [ 51 53 ]. In light of this, MSC-derived exosomes are a promising alternative strategy for the treatment of LC.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to parental MSC activity, MSC-derived exosomes [ 45 , 46 ] function as a mediator of intercellular communication between MSC and injured organ sites, which exerts effectiveness in various animal models of liver disease including acute liver damage, hepatic fibrosis, and hepatocellular carcinoma [ 47 50 ]. Typically, Exosomes are easier to obtain and store, and inherited with qualities like high reparability and low immunogenicity [ 51 53 ]. In light of this, MSC-derived exosomes are a promising alternative strategy for the treatment of LC.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all chronic liver injuries induced by different etiologies may contribute to liver fibrosis ( Lai and Afdhal, 2019 ; Liu et al, 2023 ). When a liver develops fibrosis, a large number of extracellular matrices, such as collagen Ι, will deposit excessively since quiescent HSCs are activated into contractile myofibroblast-like cells ( Brempelis and Crispe, 2016 ; Xu et al, 2016 ; Lyu et al, 2023 ; Zhang et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…MAPK pathways, such as p38 MAPK and ERK, are significant for cell growth and differentiation, and closely associated with liver fibrosis (Li et al, 2016). Previous evidence has demonstrated that the MAPK pathway is related to NF-κB activation stimulated by lipopolysaccharide (LPS) (Guha and Mackman, 2001;Wu et al, 2023). It is worth noting that both MAPK and NF-κB are regarded as classical and key anti-inflammatory pathways, and MAPK can activate NF-κB to regulate inflammatory processes (Kim et al, 2019;Ren et al, 2020;Tang et al, 2021).…”
Section: Schizandrin C Inhibits the P38/erk Mapk Signaling Pathwaymentioning
confidence: 99%
“…Exosomes have emerged as a significant therapeutic entity in the management of diverse fibrotic maladies, with exosomes from various sources and their molecular cargoes—such as miRNAs, lncRNAs, and proteins—being contemplated as targeted therapeutic interventions. These entities can influence an array of cellular types and signal transduction pathways implicated in fibrosis ( 57 , 58 ).…”
Section: Exosomes In Sports Medicine-related Researchmentioning
confidence: 99%